2008
DOI: 10.1080/10871200802277716
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Recovery: Wisconsin's Wolf Policy 1980–2008

Abstract: Wildlife protectionists, livestock producers, and black bear hunters influenced wolf policy in Wisconsin, USA, over the past 29 years. Wolf policy aligned closely with protectionist values until 2003, when litigations over lethal control and wolf reclassification created a rift. Since 2003, livestock producers and bear hunters have had more influence over wolf policy. Throughout, state managers steered steadily toward regaining management authority from the federal government and finding common ground between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Moral hazards are more likely to arise when recipients have disproportionate influence over rules for payments. We observed that contributors held less sway than recipients because contributors donated anonymously, limiting their effectiveness as a lobbying group (Treves 2008). After the final compensation rule was published in 2005, several contributors wrote letters to the WDNR opposing the use of their money to pay for hunting dogs injured or killed by wolves (R. Jurewicz, WDNR files).…”
Section: Compensation Is Popularmentioning
confidence: 96%
See 2 more Smart Citations
“…Moral hazards are more likely to arise when recipients have disproportionate influence over rules for payments. We observed that contributors held less sway than recipients because contributors donated anonymously, limiting their effectiveness as a lobbying group (Treves 2008). After the final compensation rule was published in 2005, several contributors wrote letters to the WDNR opposing the use of their money to pay for hunting dogs injured or killed by wolves (R. Jurewicz, WDNR files).…”
Section: Compensation Is Popularmentioning
confidence: 96%
“…As wolf numbers increased, it also became far more costly to verify every incident. In 2001 the WDNR compensated a livestock producer for missing calves based on prior verified losses without direct evidence of wolf predation (Treves 2008). In 2007, this step was formalized and extended to all livestock producers with previously verified losses (WDNR 2007a, b).…”
Section: History Of Wolf Compensation In Wisconsinmentioning
confidence: 99%
See 1 more Smart Citation
“…Muro & Jeffrey 2008;www.humanwildlifeconflict.org). For wildlife and endangered species, participatory planning can also increase understanding about the root causes for conflict and the possible focal points for successful interventions (Treves 2008, Treves et al 2009). Such approaches have also been shown to increase local capacity and build stewardship among communities for more effective conservation Like other species that have begun repopulating previous ranges, the Hawaiian monk seal is presenting new challenges to conservation programs as new values and evolving social norms for the species develop.…”
Section: Applying Sociocultural Dimensions To Species Conservation Plmentioning
confidence: 99%
“…Human−wildlife conflicts can develop through a myriad of different pathways, but are based in part on the underlying social values, norms and perceptions that structure human−environmental interactions. Stakeholders may exhibit a range of values for endangered wildlife (Kellert 1985, Treves 2008, and these values, like other social phenomena, are not static but evolve through time.…”
Section: Introductionmentioning
confidence: 99%